2021
DOI: 10.1021/acs.jpclett.1c01094
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Promotes the Formation of MoSe2 at the Interface of Cu2ZnSnSe4/Mo

Abstract: The contact, and thus the hole collection between Cu2ZnSnSe4 (CZTSe) and Mo, is a crucial issue to improve the performance of CZTSe solar cells. In this work, a method to improve the back contact is explored by spraying Na3PO4 on the surface of the Mo back contact. With the O provided from Na3PO4, extra MoO2 and MoO3 are formed at the surface of the back contact, and partial MoO2 is transformed into MoSe2 under high Se2 partial pressure during the selenization process. The formation of MoSe2 progresses from di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, the excessively loose film is not beneficial for selenization. On the one hand, Se vapor is easily penetrated into the film and reacts with the Mo layer to form a thick MoSe 2 layer, which will increase R s [31,32]. On the other hand, the penetrated Se facilitates the formation of a Cu 2−x Se fluxing agent at the bottom of the film and hence a double-large grain layer absorber structure finally form (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the excessively loose film is not beneficial for selenization. On the one hand, Se vapor is easily penetrated into the film and reacts with the Mo layer to form a thick MoSe 2 layer, which will increase R s [31,32]. On the other hand, the penetrated Se facilitates the formation of a Cu 2−x Se fluxing agent at the bottom of the film and hence a double-large grain layer absorber structure finally form (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is well consistent with Mo electrodes in substrate structured Sb 2 S 3 , as well as CIGS, CZTSSe solar cells. [ 21 ] The conductivity, one of the most appealing characters of the metal electrodes, is further explored on devices by a four‐point probe test (Figure 2b ). It is concluded that the square resistance of the Mo deposited on Sb 2 S 3 surface (5.6 Ω □ –1 ) is not distinctly different from that on the glass substrate (5.4 Ω □ –1 ) in the same thickness of ≈900 nm under the standard sputtering process.…”
Section: Resultsmentioning
confidence: 99%
“…Over 14% efficiency has been achieved for CZTSSe-based solar cells by regulating the phase evolution kinetics of Ag-doped CZTSSe in a positive pressure . In addition, to inhibit the carrier recombination at the back interface, numerous attempts of back interface engineering have been implemented. For example, a TiN or Al 2 O 3 passivation layer was inserted between the CZTSSe absorber and Mo back electrode to prevent the formation of secondary phases in the absorber and reduce the thickness of MoSe 2 by inhibiting the interfacial reaction. A VSe 2 or MoO x intermediate layer with high work function ( W F ) was inserted between the CZTSSe absorber and Mo back electrode to boost hole extraction and reduce the MoSe 2 thickness.…”
Section: Introductionmentioning
confidence: 99%